2021
DOI: 10.7759/cureus.13164
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of End-Tidal Carbon Dioxide as a Marker for Fluid Responsiveness in Cardiogenic Shock

Abstract: Baloch et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In agreement with the current study, previous studies have revealed that ΔETCO2 ≥5% or ΔETCO2 >2 mmHg can predict fluid responsiveness to PLR in haemodynamically unstable patients. [ 2 , 5 , 15 ] The current study proved higher predictivity of FC-induced ΔETCO2 ≥2 mmHg (area under the ROC curve [AUC] 0.908) than that of Baloch et al .’s[ 16 ] study including cardiogenic shock patients (AUC 0.705) and Jacquet-Lagrèze et al .’s[ 17 ] study carried out for high-risk surgical patients (AUC 0.800). Heterogenicities between different studies assessing the predictivity of FC-induced ΔETCO2 for fluid responsiveness may be due to different standard references or fluid-loading techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the current study, previous studies have revealed that ΔETCO2 ≥5% or ΔETCO2 >2 mmHg can predict fluid responsiveness to PLR in haemodynamically unstable patients. [ 2 , 5 , 15 ] The current study proved higher predictivity of FC-induced ΔETCO2 ≥2 mmHg (area under the ROC curve [AUC] 0.908) than that of Baloch et al .’s[ 16 ] study including cardiogenic shock patients (AUC 0.705) and Jacquet-Lagrèze et al .’s[ 17 ] study carried out for high-risk surgical patients (AUC 0.800). Heterogenicities between different studies assessing the predictivity of FC-induced ΔETCO2 for fluid responsiveness may be due to different standard references or fluid-loading techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is limited as the predictivity of ETCO2 variation for fluid responsiveness cannot be applied to either spontaneously breathing patients or in the presence of metabolic or ventilatory changes. [ 4 , 16 ] IJVDI is a priori predictor of fluid responsiveness, while ΔETCO2 is a posteriori predictor, and FC, which was used to induce CO 2 change, is not just a test, but it is a treatment option that, if repeated, can lead to volume overload. So, it is recommended to use FC-induced ΔETCO2 if fluid administration is strongly indicated (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, dynamic indicators of fluid responsiveness, which are based on cardiopulmonary interactions in patients receiving mechanical ventilation, have been shown to be predictive [ 38 42 ]. The ΔEtCO 2 has been extensively studied with respect to its value in predicting fluid responsiveness, but the results are conflicting [ 13 18 , 30 – 33 , 43 – 45 ]. To the best of our knowledge, this is the first systematic review and meta-analysis to explore the diagnostic accuracy of ΔEtCO 2 in predicting fluid responsiveness during PLR test in patients with mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…EtCO 2 has also been shown to correlate with cardiac output after weaning from CPB and predicts adequate post-bypass cardiac output [ 12 ]. Changes in etCO 2 have also been studied as a way to identify changes in cardiac output in anaphylaxis during general anesthesia [ 13 ], hemorrhage [ 14 ], and septic shock [ 15 ], and as a useful bedside test to predict fluid responsiveness in cardiogenic shock [ 16 ].…”
Section: Discussionmentioning
confidence: 99%